Implementasi Potensi Lokal dalam Pembelajaran IPA: Studi Pengembangan LKPD Berbasis Lingkungan - Wilujeng, Insih; Purwasih, Desy; Widowati, Asri; Widowati, Susilowati (Carmin: Journal of Community Service, 2024)
Local potential is the potential of certain resources owned by an area including the environment, natural resources, people, technology, and culture that can be developed to build national independence. Science learning in schools should not be limited to transferring theories but, there must be a process of natural investigation. The activities were conducted to improve the ability of teachers to design science observation and experiment activities based on environmental potential. Activities were carried out as many as four meetings in a blended manner, namely online and offline. At the beginning of the activity, coordination was carried out with the Science Teacher Group in Yogyakarta. There were 30 participants who participated in the training with a background of science teachers and students. Evaluation of activities is measured through attitude scale instruments and assessment rubrics. There are two types of attitude scales used, namely open and closed attitude scales. The material presented in the form of an introduction to local potential, and the use in the classroom as outlined in the LKPD. The results showed that the greatest understanding of local potential was shown in the benefits indicator with a value of 78.6. While the others, namely the lowest experience indicator with an average of 53.6 while knowledge with a value of 74.6 and application of 57.1. Teachers who can integrate local potential in science learning such as traditional apem wonolelo can be integrated with the concept of temperature, saparan bekakak ceremony can be used in the concept of substances mixture, making pottery heat can be interagted in the concept of pressure, measurement, etc. This service is useful to increase teacher innovation in learning.